Digital Image Correlation parameters optimized for the characterization of fatigue crack growth life. (April 2021) - Sánchez, M.; Mallor, C.; Canales, M.; Calvo, S.; Núñez, J.L.
Highlights: DIC and Williams' series as alternative to the COD extensometer for fracture mechanics. The DIC is used to measure the field of displacements on a MT specimen under mode I. The optimal parameters of the DIC and Williams' series are found for the MT specimen. Differences about 1% for d a d N v s Δ K curve obtained by DIC and traditional method. The method enables to obtain the crack growth rate of any type of component and loads. Abstract: This paper presents a novel methodology to obtain the fatigue crack growth rate versus the stress intensity range, d a / d N v s Δ K curve, by only using the digital image correlation (DIC) technique. First, an optimization of the DIC and William's series parameters is performed. The optimal parameters are obtained by comparison with reference calculations performed by the extended finite element method. Finally, the DIC technique considering the previous results is used to characterize the fatigue crack growth process on a standard middle tension (MT) specimen under mode I loading to build up the d a / d N v s Δ K curve. The differences in the characterization using the DIC and traditional measurements range from the 14% and the 3% for stress intensity factors (SIFs) between 14 and 18 MPa√m, and about 1% for SIFs between 18 and 36 MPa√m. The fatigue crack growth curve obtained is checked by comparison with traditional measurement methods.